Academic writing and referencing for your education degree - Bottomley, Jane (Senior language tutor); Pryjmachuk, Steven, 1964-; Waugh, David (David G.) (Critical study skills for education students., 2018)
Gives you with a sound knowledge and understanding of what constitutes good academic writing in education through a range of strategies for writing successful essays and reports. Emphasises the importance of clarity and coherence in your writing about education and advises how to improve your academic style, grammar and punctuation, and formatting and presentation.